Answer:
Option (2)
Explanation:
Given expression is, AX + B = C
![A=\begin{bmatrix}-3 & -4\\ 1 & 0\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/i0igm95i7c7bzsz3939omd7cltt3akv1jx.png)
![B=\begin{bmatrix}-7 & -9\\ 4 & -1\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/eeoyv4fyg19gu56sqclrmd6gzgp9ksz3jf.png)
![C=\begin{bmatrix}-42 & -20\\ 5 & 4\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/8vvsc4xnvy7ssyrjwnzozzcnj8awgjs2s6.png)
AX + B = C
AX = C - B
C - B =
=
![\begin{bmatrix}-42+7 & -20+9\\ 5-4 & 4+1\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/oqw0oprxcpr725ntndjl2p0aago4raz4az.png)
C - B =
![\begin{bmatrix}-35 & -11\\ 1 & 5\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/z3uszbje6avalqlg0kcalibyg3bgn81bij.png)
Let
![X=\begin{bmatrix}a & b\\ c & d\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/her61tt8y5s3zvyoea23pzmh3kzuehpmxa.png)
AX =
=
![\begin{bmatrix}(-3a-4c) & (-3b-4d)\\ a & b\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/41odp7cynncukh2goohccb6tf6tuczv67k.png)
Since AX = C - B
![\begin{bmatrix}(-3a-4c) & (-3b-4d)\\ a & b\end{bmatrix}=\begin{bmatrix}-35 & -11\\ 1 & 5\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/college/dxinh85v4phbrw14fv5wae8zz4rqyiacct.png)
Therefore, a = 1, b = 5
(-3a - 4c) = -35
3(1) + 4c = 35
3 + 4c = 35
4c = 32
c = 8
And (-3b - 4d) = -11
3(5) + 4d = 11
4d = -4
d = -1
Therefore, Option (2). X =
will be the answer.